Direct voltage regulation of DC–DC buck converter in a wide range of operation using adaptive input–output linearization. Issue 1 (14th November 2014) - Salimi, Mahdi; Zakipour, Adel
<x xml:space="preserve">Abstract</x> In this paper, an adaptive nonlinear controller is designed for voltage control of the DC–DC buck converter in both continuous and discontinuous conduction modes. The proposed controller is developed based on input–output linearization, which is robust and stable against converter load changes, input voltage variations, and parameter uncertainties. In the proposed approach, all the converter parameters, namely input voltage, load resistance, and other parasitic elements of the power circuit, are assumed to be uncertain and estimated using a suitable Lyapunov function. Using a stand‐alone TMS320F2810 digital signal processor from Texas Instruments, some simulations and experimental results are obtained to verify the proposed control approach. The results are in good agreement and prove the effectiveness and capability of the controller over a wide range of operations. Also, advantages of the designed nonlinear regulator are indicated in comparison with a pulse width modulation (PWM)‐based sliding mode controller. © 2014 Institute of Electrical Engineers of Japan. Published by John Wiley & Sons, Inc.